Innovative Training in Cocoa Agroforestry : The Farmer Field Schools of Nicaragua - Gonzalez, Mary Lisbeth (World Bank, Washington, DC, 2012)
The World Bank, with the financial support of the Japan Social Development Fund (JSDF), is implementing the Alternative Indigenous and Afro-Descendants and Agroforestry Project (COCOA-RAAN) in the indigenous and Afro-descended (Miskito) regions of Nicaragua. The implementing agency, the Agro-forestry coordinating association of indigenous peoples and farmers, is a regional Non government Organization (NGO) 'focused on seeking local socio-productive integration, promoting ecodevelopment and community empowerment.' The project's objective is to strengthen the capacity of indigenous, Miskito, and mestizo organizations to produce and market quality cocoa in an economically and environmentally sustainable manner. The project is designed to transform the environmentally damaging practices of cocoa agriculture to conserve the biodiversity, regenerate and sustainably manage forest resources, and improve farmers' livelihoods. Activities include interventions to: i) develop integrated management systems for agro-forestry on at least 1,000 cocoa small farmers; ii) improve marketing to international fair trade and sustainable chocolate companies; and iii) strengthen the social, commercial and environmental management capacity of beneficiaries. To reach the beneficiary community-based organizations and cooperatives, a project-sponsored fund finances subprojects of up to US$25,000.